Association between Cervical Lymph Node Metastasis and the Incidence of Radiation-Induced Hypothyroidism in Nasopharyngeal Carcinoma. (1st February 2022) - Zhou, Ling; Chen, Jia; Tao, Chang-Juan; Zhao, Qing-Feng; Chen, Yu-Ming; Chen, Xiao-Zhong; Chen, Ming; Yu, Zhong-Hua; Chen, Yuan-Yuan
Abstract : Background . It is controversial and unclear how N -stage would increase the risk of incidence of hypothyroidism (HT) for patients with nasopharyngeal carcinoma (NPC) after radiotherapy. Our study aimed to explore the correlation between cervical lymph node metastasis and the incidence of HT in NPC. Materials and Methods . A total of 206 patients with NPC treated at the Cancer Hospital of University of Chinese Academy of Sciences, and their clinical information were retrospectively collected. A series of univariate logistic regression models were performed to explore the association of clinical and lymph node indices with the development of HT. Significant features in univariate analysis were then used to construct three prediction models, for HT prediction using multivariate logistic regression based on Bayesian information criterion. Prediction performance of those models was measured by area under the receiver operating characteristic curve (AUC) using 10-fold cross-validation. Results . A total of 111 patients developed HT, and the incidence of HT in N 2–3 and N 0–1 patients was 58.82% and 44.29%, respectively. Compared to Model 1 (consisted of pretreatment TSH concentration, thyroid volume, and N -stage) whose AUCs were 0.801 and 0.766 in training and validation sets, with N -stage be replaced by shortest distance from thyroid, Model 2 achieved more stable AUCs of 0.824 and 0.801. While with numbers of positive lymph nodes in Level IIb additionally added, Model 3 improved its AUCs to 0.841 and 0.813. Conclusion . The shortest distance between the lymph nodes and thyroid gland and the number of lymph nodes in IIb are better predictors of radiation-induced HT than the N -stage.